2014
DOI: 10.6106/jcepm.2014.4.1.037
|View full text |Cite
|
Sign up to set email alerts
|

A Health and Safety Improvement Roadmap for the Construction Industry

Abstract: Comparatively, the construction industry has, on average, a higher rate of fatal and major injuries, work induced illhealth and damage to properties than other industrial sectors; and this is a source of concern to industry stakeholders. The study showed that although subcontracting could be contributory to an increase in workplace accidents in the construction industry, contractual aspects of subcontracting arrangements (such as the power imbalance that exist along the client-customer interface) also present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Gambatese and Behm (2008) opine that despite the numerous ongoing research, accident still occurs. Diugwu and Baba (2014) suggested that, successful delivery of the project depends on the level of compliance with safety regulations. This has led to the establishment of Occupational Safety and Health Administration (OSHA) to enforce safety laws and regulations (Jaselskis, Anderson & Russel 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Gambatese and Behm (2008) opine that despite the numerous ongoing research, accident still occurs. Diugwu and Baba (2014) suggested that, successful delivery of the project depends on the level of compliance with safety regulations. This has led to the establishment of Occupational Safety and Health Administration (OSHA) to enforce safety laws and regulations (Jaselskis, Anderson & Russel 1996).…”
Section: Introductionmentioning
confidence: 99%